Space vector pulse width modulation realization for three-phase voltage source inverter - Palanisamy, Ramasamy; Santhakumari, Valarmathi Thangamani; Venkatarajan, Shanmugasundaram; Hemalatha, Selvaraj; Hepzibah, Albert Alice; Ramkumar, Ravindran; Sugavanam, Vidyasagar (Institute of Advanced Engineering and Science, 2024)
This paper presents the implementation of space vector pulse width modulation (SVPWM) for a three-phase voltage source inverter (VSI). SVPWM is a technique used to control the output voltage of VSIs with improved efficiency and precision. The abstract outlines the key steps involved in implementing SVPWM, including reference signal clarification, sector identification, determination of voltage vectors, and switching state calculation. This proposed system provides improved output voltage of the inverter, minimized voltage stress across the switches and reduced total harmonic distortion and electromagnetic interference. The proposed implementation aims to enhance the performance of three-phase VSIs in various applications, such as motor drives, renewable energy systems, and power converters. The simulation results of proposed system are verified using MATLAB Simulink.